The Effect of 3M Educational Intervention on Parents’ Knowledge in Preventing Dengue Hemorrhagic Fever (DHF) - Affila Hanindar Aspasya Putri; Berliany Venny Sipollo; Yafet Pradikatama Prihanto (Jurnal Kesehatan Cendikia Jenius, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in tropical countries, including Indonesia, with its incidence closely related to inadequate knowledge and preventive practices at the household level. The 3M strategy (draining, covering, and burying) is a key preventive approach that requires active parental involvement. This study aimed to determine the effect of 3M educational intervention on parents’ knowledge in preventing DHF. A quantitative study with a one-group pretest–posttest design was conducted. The sample consisted of 52 parents selected using total sampling. Data were collected using a structured knowledge questionnaire administered before and after the 3M educational intervention, conducted from January to March 2024 in the working area of Ardimulyo Public Health Center. Data were analyzed using the Wilcoxon Signed-Rank test. The results showed a significant increase in parents’ knowledge levels after the intervention, with a marked rise in the proportion of respondents classified as having good knowledge. Statistical analysis revealed a p-value < 0.05, indicating a significant effect of the 3M educational intervention on parents’ knowledge. In conclusion, 3M education effectively improves parents’ knowledge in preventing DHF. Continuous and structured health education programs are recommended as sustainable preventive strategies to reduce DHF incidence at the community level.